Glasbeno izobraževanje v ljubljanskih šolah v drugi polovici 16. in na začetku 17. stoletja - Grabnar, Klemen (De musica disserenda, 2011)
The contribution presents the musical activities which took place in the four main educational institutions in Ljubljana: the Protestant German school, the Latin school, the Cathedral school of St. Nicholas, and the Jesuit college, covering the period from ca. 1550 to ca. 1630. Also mentioned are the musical activities at the school at the monastery of the Teutonic order in Ljubljana.
Keywords: glasbena vzgoja in izobraževanje; Ljubljana (Slovenija); zgodovina; history; 16./17.st.